PENGARUH MODEL PROJECT BASED LEARNING MENGGUNAKAN MEDIA SCRAPBOOK MATERI KEHIDUPAN MASYARAKAT PADA MASA KERAJAAN HINDU BUDDHA DI INDONESIA TERHADAP KREATIVITAS PESERTA DIDIK KELAS VIII SMP NEGERI 6 SURABAYA - Raissa Shafa Camilla Noor; Dhimas Bagus Virgiawan; Niswatin; Riyadi (STKIP Subang, 2026)
Students' creativity is one of the major challenges in Social Studies (IPS) learning, as classroom instruction is still predominantly teacher-centered. This condition limits students' opportunities to develop ideas, collaborate with peers, and produce creative learning outcomes. Therefore, innovative learning models are needed to foster students' creativity. This study aimed to determine the effect of the Project Based Learning model assisted by scrapbook media on students' creativity in the topic of community life during the Hindu-Buddhist Kingdoms in Indonesia. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of 68 eighth-grade students at SMP Negeri 6 Surabaya, divided into an experimental class and a control class through purposive sampling. Data were collected using observations, creativity questionnaires, pre-tests, post-tests, and documentation. The data were analyzed through normality tests, homogeneity tests, and an independent samples t-test. The results indicated a significance value (Sig. 2-tailed) of 0.000 (< 0.05), demonstrating a statistically significant difference between the experimental and control groups. The experimental class achieved a higher mean creativity score than the control class, with a mean difference of 8.794. These findings indicate that the implementation of the Project Based Learning model assisted by scrapbook media significantly improves students' creativity. Through project-based learning activities, students are encouraged to explore ideas, collaborate actively, solve problems, and create meaningful learning products, thereby enhancing their creative abilities. Consequently, the Project Based Learning model integrated with scrapbook media can serve as an effective instructional strategy for improving students' creativity in Social Studies learning.